2017
DOI: 10.1021/acs.jpcb.7b00649
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of Cyanocobalamin and Its Conjugates with Peptide Nucleic Acids

Abstract: Vitamin B also called cobalamin (Cbl) is an important enzymatic cofactor taken up by mammalian and also by many bacterial cells. Peptide nucleic acid (PNA) is a synthetic DNA analogue that has the ability to bind in a complementary manner to natural nucleic acids. Provided that PNA is efficiently delivered to cells, it could act as a steric blocker of functional DNA or RNA and regulate gene expression at the level of transcription or translation. Recently, Cbl has been examined as a transporter of various mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Most effective is a conjugate with PNA anchored at the R 5′ ‐OH group, whereas modifications at the peripheral c , e , and meso positions adversely affect the uptake; thus indicating the importance of c‐ and e ‐amides during the recognition process. The PNA forms compact structures in solution, but its flexibility (required for hybridization with RNA) increases upon the attachment of vitamin B 12 at the R 5′ ‐OH position, as previously found by us in molecular dynamics simulations . However, the structural dynamics of PNA attached at other vitamin B 12 positions is yet to be elucidated.…”
Section: Resultssupporting
confidence: 59%
“…Most effective is a conjugate with PNA anchored at the R 5′ ‐OH group, whereas modifications at the peripheral c , e , and meso positions adversely affect the uptake; thus indicating the importance of c‐ and e ‐amides during the recognition process. The PNA forms compact structures in solution, but its flexibility (required for hybridization with RNA) increases upon the attachment of vitamin B 12 at the R 5′ ‐OH position, as previously found by us in molecular dynamics simulations . However, the structural dynamics of PNA attached at other vitamin B 12 positions is yet to be elucidated.…”
Section: Resultssupporting
confidence: 59%
“…In recent years, PNA was combined with vitamin B 12 using different linkers. Vitamin B 12 was also found to improve PNA solubility and make the PNA in the conjugate adopt a more extended conformation in comparison with free single-stranded PNA [124]. Furthermore, we have shown that vitamin B 12 acts as a carrier of PNA to E. coli and Salmonella enterica subsp.…”
Section: Delivery Of Pna To Bacteriamentioning
confidence: 68%
“…Screening of further bacterial mRNA virulence targets and assessment of optimal ASO lengths to balance specificity and bacterial cell entry are also additional areas for study. Recently the fact that some bacteria are capable of vitamin B12 uptake was exploited to achieve enhanced PNA delivery into S. typhimurium and E. coli by a novel conjugation of PNA antisense oligomers to vitamin B12 (Pieńko et al 2017; Równicki et al 2017). These PNA-B12 conjugates were synthesized by a Cu-catalyzed 1,3-dipolar cycloaddition of the vitamin B12 azide to PNAs possessing a terminal alkyne group.…”
Section: Future Challenges and Prospectsmentioning
confidence: 99%